Manajemen Impresi Penyiar Radio Play99ers Bandung - Alzalika Tariqa Sugardo; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. Unconsciously people often peform impression management, but also consciouly for certain personal, financial, social, and politic. Considering the profession of radio announcer is indeed included in the field of communication, as a communicator and also as a profession that requires the individual to have a positive impression or self image in the community. The research aims to bring up: (1) How Impression Management in Front Stage Life of an Announcer on Play99ers Radio, (2) How Impression Management in Back Stage Life of an Announcer on Play99ers Radio, (3) How an Announcer on Play999ers Radio Plays a Role in Playing the Character, (4) How a Play99ers Radio Announcer Builds Self Image Towards Listeners, (5) Knowing and Understanding Why Announcer on Play99ers Radio Perform Impression Management. Researchers use qualitative methods with dramaturgy studies, by conducting observations, in-depth interview, and documentation as a data collection techniques. The results of this study are 1) In the Front Stage, Dara wants to show herself as a friendly, insightful, and interactive announcer 2) In the Back Stage, Dara prioritizes the preparation of material before the broadcast, and in the Back Stage dara shows some differences in appearance and nature and shows dara's true identity. 3) The role displayed to the listener is adapted to the character that Dara has so that the listeners can remember and also be known by the wider community. 4) The self-image built by Dara produces an insightful announcer character, as is, such as his friendly attitude then easily blends in. 5) The reason why Sevia Dara does impression management is so that it can be known by listeners and also others in accordance with the character and skills that she has Abstrak. Secara tidak sadar orang-orang sering melakukan manajemen kesan, tetapi juga secara sadar untuk keuntungan pribadi, finansial, sosial dan politik tertentu. Mengingat profesi penyiar radio ini memang termasuk dalam bidang komunikasi, sebagai seorang komunikator dan juga sebagai profesi yang menuntut individu tersebut mempunyai kesan atau citra diri yang positif di masyarakat. Penelitian ini bertujuan untuk mengemukakan: (1) Bagaimana Manajemen Impresi di Kehidupan Panggung Depan (Front Stage) Seorang Penyiar di Play99ers Radio, (2) Bagaimana Manajemen Impresi di Kehidupan Panggung Belakang (Back Stage) Seorang Penyiar di Play99ers Radio, (3) Bagaimana Seorang Penyiar di Play99ers Radio Bermain Peran dalam Memainkan Karakternya, (4) Bagaimana Cara Penyiar Play99ers Radio Membangun Citra Diri (Self Image) Terhadap Pendengar, (5) Mengetahui dan Memahami Mengapa Penyiar di Play99ers Radio Melakukan Manajemen Impresi. Peneliti menggunakan metode kualitatif dengan studi dramaturgi, dengan melakukan observasi, wawancara mendalam, dan dokumentasi sebagai teknik pengumpulan data. Hasil dari penelitian ini adalah 1) Dalam Front Stage, Dara ingin menunjukkan dirinya sebagai announcer yang ramah, berwawasan luas, dan juga interactive 2) Dalam Back Stage, Dara lebih mengutamakan persiapan materi sebelum siaran, dan dalam Back Stage pula Dara menunjukkan beberapa perbedaan penampilan dan sifat serta menunjukkan jati diri Dara yang sesungguhnya. 3) Peran yang ditampilkan kepada pendengar disesuaikan dengan karakter yang Dara punya sehingga para pendengar bisa mengingat dan juga dikenal oleh masyarakat luas. 4) Citra diri yang dibangun oleh Dara menghasilkan karakter announcer yang berwawasan luas, apa adanya, seperti sikapnya yang ramah kemudian gampang berbaur. 5) Alasan mengapa Sevia Dara melakukan impression management adalah agar bisa dikenal oleh para pendengar dan juga orang lain sesuai dengan karakter serta skill yang ia punya.